2011
DOI: 10.1001/jama.2011.1141
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Asymptomatic Isolated Microscopic Hematuria in Israeli Adolescents and Young Adults and Risk for End-Stage Renal Disease

Abstract: Presence of persistent asymptomatic isolated microscopic hematuria in persons aged 16 through 25 years was associated with significantly increased risk of treated ESRD for a period of 22 years, although the incidence and absolute risk remain quite low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
145
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(151 citation statements)
references
References 30 publications
2
145
1
2
Order By: Relevance
“…This fact may be in part due to the difficulty in assessing microscopic hematuria quantitatively [25,26]. Recently, Vivante et al reported that persistent asymptomatic isolated microscopic hematuria was significantly associated with increased risk of ESRD over 22 years of follow-up in 1.2 million persons aged 16 through 25 years [4]. This study suggests that hematuria in the absence of a specific diagnosis can be a risk factor of ESRD and the classical term "benign hematuria" or "benign familial hematuria" may be a misnomer, especially in most cases where neither a histopathologic nor a genetic diagnosis is made [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact may be in part due to the difficulty in assessing microscopic hematuria quantitatively [25,26]. Recently, Vivante et al reported that persistent asymptomatic isolated microscopic hematuria was significantly associated with increased risk of ESRD over 22 years of follow-up in 1.2 million persons aged 16 through 25 years [4]. This study suggests that hematuria in the absence of a specific diagnosis can be a risk factor of ESRD and the classical term "benign hematuria" or "benign familial hematuria" may be a misnomer, especially in most cases where neither a histopathologic nor a genetic diagnosis is made [4].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Vivante et al reported that persistent asymptomatic isolated microscopic hematuria was significantly associated with increased risk of ESRD over 22 years of follow-up in 1.2 million persons aged 16 through 25 years [4]. This study suggests that hematuria in the absence of a specific diagnosis can be a risk factor of ESRD and the classical term "benign hematuria" or "benign familial hematuria" may be a misnomer, especially in most cases where neither a histopathologic nor a genetic diagnosis is made [4]. Goto et al also showed that mild hematuria was associated with increased risk of ESRD over 10 years of follow-up in 790 IgA nephropathy patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study IMH was diagnosed in 3690 of 1,203,626 individuals who were 16 through 25 years of age. During 22 years of follow-up, ESRD developed in 26 (0.7%) individuals with IMH and 539 (0.045%) with other causes like diabetes, hypertension, hereditary nephritis, interstitial nephritis, and cystic kidney diseases (14). We also closely followedup for up to 15 years the children in which we had not performed biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper Vivante A et Al found an increase of incidence of ESRD in patients (aged 16 to 25 year) with persistent asymptomatic isolated microscopic hematuria [54]. In 2011 a meta-analysis found that albuminuria is a risk factor for all-cause and cardiovascular mortality in high-risk populations [55].…”
Section: Hematuria and Proteinuriamentioning
confidence: 99%